OPTIMALISASI PENGELOLAAN DEPO SAMPAH KOTA LANGSA BERBASIS KEUANGAN BERKELANJUTAN DENGAN ANALISIS SOAR - Ridha Azkiya; Cut Vita Rajjatul Jummi; Dazka Azis (Jurnal Mahasiswa Akuntansi Samudra, 2024)
Garbage in Indonesia is a problem that must be found a solution. Every time the amount of waste always increases, making the surrounding environment dirty and dirty, this requires the awareness of the government and society to handle it. The purpose of this research is to find an effective strategy for dealing with waste, especially in Langsa City. This study uses the soar analysis method where the expected results can be a good strategy. The results of this study are: Making regulations with integrity by the environmental service, Waste care movement regulated by the village government, Allocation of village funds for waste handling, Separation of organic and inorganic household waste, Utilization of waste to Reuse, reduce, Reycycle, Using the most efficient route for the waste disposal channel, conducting outreach to the public to care for the environment.